2021
DOI: 10.3389/fpls.2021.651262
|View full text |Cite
|
Sign up to set email alerts
|

A Rationally Designed Bovine IgA Fc Scaffold Enhances in planta Accumulation of a VHH-Fc Fusion Without Compromising Binding to Enterohemorrhagic E. coli

Abstract: We previously isolated a single domain antibody (VHH) that binds Enterohemorrhagic Escherichia coli (EHEC) with the end-goal being the enteromucosal passive immunization of cattle herds. To improve the yield of a chimeric fusion of the VHH with an IgA Fc, we employed two rational design strategies, supercharging and introducing de novo disulfide bonds, on the bovine IgA Fc component of the chimera. After mutagenizing the Fc, we screened for accumulation levels after transient transformation in Nicotiana bentha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 72 publications
0
4
1
Order By: Relevance
“…We also introduced a de novo disulfide pair G196C/R219C into the V H H-Fc targeted with the Sec signal and found a significant yield improvement. Compared to the ten-fold yield improvement observed previously when targeted to the ER (Chin-Fatt et al, 2021), the yield improvement is substantially less at only about a two-fold improvement. This may possibly be due to the availability of relevant chaperones across the two compartments.…”
Section: Disulfide Formation In the Chloroplastcontrasting
confidence: 66%
See 3 more Smart Citations
“…We also introduced a de novo disulfide pair G196C/R219C into the V H H-Fc targeted with the Sec signal and found a significant yield improvement. Compared to the ten-fold yield improvement observed previously when targeted to the ER (Chin-Fatt et al, 2021), the yield improvement is substantially less at only about a two-fold improvement. This may possibly be due to the availability of relevant chaperones across the two compartments.…”
Section: Disulfide Formation In the Chloroplastcontrasting
confidence: 66%
“…We have previously identified by rational design a residue pair (G196C/R219C) on the Fc that if mutated to cysteines would form a de novo disulfide bond that enables a ten-fold improvement in yield of the V H H-Fc when targeted to the ER (Chin-Fatt et al, 2021). The pair forms an intra-chain disulfide between strand G and strand F on the CH3 domain in oxidative folding conditions (Figures 4A,B).…”
Section: Sec-targeted V H H-fc Fusions With An Engineered Disulfide Show Improved Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the protein’s stability, conformation, and post-translational modifications, some proteins will become more or less abundant over the first week or two before they disappear completely. Some proteins remain stable over 3-8 days ( Chin-Fatt et al., 2021 ; VanderBurgt et al., 2023 ), some increase their accumulation with time ( Saberianfar et al., 2019 ), and others reach their highest accumulation at 4-6 days and then go down with time ( Garabagi et al., 2012 ). Here, we found that accumulation levels are highest four days post-infiltration, and this is the time we subsequently harvested the infiltrated leaf material.…”
Section: Resultsmentioning
confidence: 99%